Neohesperidin suppresses IgE‐mediated anaphylactic reactions and mast cell activation via Lyn‐PLC‐Ca2+ pathway. (14th June 2019) - Zhao, Tingting; Hu, Shiling; Ma, Pengyu; Che, Delu; Liu, Rui; Zhang, Yongjing; Wang, Jue; Li, Chaomei; Ding, Yuanyuan; Fu, Jia; An, Hongli; Gao, Zijun; et al.
Abstract : Mast cells play an essential role in IgE‐FcεR1‐mediated allergic diseases. Citrus aurantium is a prolific source of flavonoids with various biological activities, including anti‐inflammatory, antioxidant, and anti‐tumor efficacies. Neohesperidin is a novel flavonoid isolated from the leaves of C. aurantium . In this study, the anti‐allergic and anti‐inflammatory potentials of neohesperidin were investigated along with its molecular mechanism. The anti‐anaphylactic activity of neohesperidin was evaluated through hind paw extravasation study in mice. Calcium imaging was used to assess intracellular Ca 2+ mobilization. The levels of cytokines and chemokines were measured using enzyme immunoassay kits. Western blotting was used to explore the related molecular signaling pathways. Neohesperidin suppressed IgE‐induced mast cell activations, including degranulation and secretion of cytokines and eicosanoids through inhibiting phosphorylation of Lyn kinase. Neohesperidin inhibited the release of histamine and other proinflammatory cytokines through a mast cell‐dependent passive cutaneous anaphylaxis animal model. Histological studies demonstrated that neohesperidin substantially inhibited IgE‐induced cellular infiltration and attenuated mast cell activation in skin tissue. In conclusion, our study revealed that neohesperidin could inhibit allergic responses in vivo and in vitro, and the molecule may be regarded as a novel agent for preventing mast cell‐immediate and delayed allergic diseases. Abstract : Neohesperidin suppress IgE‐induced mast cell‐dependent passive cutaneous anaphylaxis reactionsin mice model. Neohesperidin inhibit the release of histamine and other proinflammatory cytokines in serumin IgE‐antigen stimulated anaphylactic mice. Neohesperidin suppress IgE‐induced mast cell activations, including calcium mobilization, degranulation and secretion of cytokines and eicosanoids. Neohesperidin attenuate IgE‐induced mast cell activation through down‐regulation of Lynkinase phosphorylation level.